Mycotoxicological monitoring. Part 1. Complete mixed feed for pigs and poultry (2009–2018) - G. P. Kononenko; A. A. Burkin; Ye. V. Zotova (Ветеринария сегодня)
Results of the ten-year annual mycotoxicological testing of complete mixed feeds for pigs and poultry submitted by holdings and processing establishments located in the Northwestern, Central, Southern, Volga and Ural Federal Districts are presented. Competitive ELISA tests showed that the occurrence of T-2 toxin, deoxynivalenol, zearalenon, fumonisines B, alternariol, ochratoxin A, citrinin, mycophenolic acid, ergoalkoloids and emodin was about 5% and quantities thereof varied within one or three orders; quantities of T-2 toxin, deoxynivalenol, zearalenon, fumonisines, and ochratoxin A might exceed maximum admissible levels for feed grains. Diacetoxyscirpenol, aflatoxin В1, sterigmatocystin and cyclopiazonic acid belonged to group of rare contaminants. Level of feed contamination with T-2 toxin and emodin was found to be consistently high during the said period; in some of the years occurrence of deoxynivalenol, fumonisines as well as ochratoxin A, citrinin, mycophenolic acid and ergoalkoloids increased. In 2016–2018, mixed feed contamination with alternariol increased whereas contamination with fumonizin steadily decreased and level of zearalenon occurrence remained consistently low. Evidence for a wide occurrence of emodin known as “diarrheic factor” as well as for sporadic increase in mixed feed contamination with alternariol, citrinin, mycophenolic acid, mycotoxins having the highly dangerous toxic impact and long-term adverse effects, was detected for the first time. These data confirmed the need for their inclusion into the regulated group of substances significant for public health. General features of pig and poultry feed contamination as well as usefulness of regional surveys for intoxication risk prediction are described. Special attention is paid to the importance of the projects for creation of common information resources that could become a unique scientific basis for innovations in feed poisoning prevention. Original monitoring data systematized and summarized in the paper are given in electronic format in section Additional materials.